Elucidating the impact of influent pollutant loadings on pollutants removal in agricultural waste-based constructed wetlands treating low C/N wastewater. (February 2019) - Wang, Ruigang; Zhao, Xin; Liu, Hai; Wu, Haiming
Graphical abstract: Highlights: High removal efficiency of COD (97%), NH4 + -N (99%), and TP (80%) was detected. Adding agricultural materials into wetland systems increased the N2 O emission. N2 O emissions from wetland systems increased with increasing influent strengths. Abstract: In this study, the common agricultural wastes (wheat straw, apricot pit and walnut shell) were exploited as the potential organic substrates in subsurface flow CWs (SSFCWs) with intermittent aeration to investigate the impacts of the varied influent loadings on the removal performance of pollutants. The results indicated that an application of agricultural wastes in CWs presented the different role in improving removal efficiency as influent pollutant loadings increased. In middle and high influent pollutant loadings, CWs with walnut shell strengthened the denitrification process significantly, and could achieve preferable purification of COD (97.36%), NH4 + -N (98.83%), TN (51.78%), and TP (80.33%), respectively. However, N2 O emission fluxes were higher in CWs with agricultural biomass and increased clearly as the influent pollutant loadings increasing. The results indicated that combination of agricultural material addition and aeration could be an appropriate intensifying strategy in SSFCWs especially for treating medium-strength low-carbon wastewaters.